2014
DOI: 10.1590/1516-1439.222313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of desulfurization of diesel and its blends with biodiesel on metallic contact

Abstract: The current environmental scenario has required changes in fuel nature, in order to minimize the harmful effects caused by sulfur in diesel. However, reductions in sulfur content promote loss of its lubricity and consequently wear in the injection system of the diesel engine. This study aimed to investigate the influence of sulfur minimization on fuel lubricity and wear of metallic disks. The fuel tribological analysis was carried out in HFRR equipment in accordance with ASTM D 6079-04. The tested fuels were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…The response surface generated for percentage of film formation (Figure 05) for fuel and concentration showed that high percentage of film formation is reached for the concentration levels above of center and high point. These results are consistent with the literature [4,5,6,8]. The biodiesel lubricity is due to the presence of a polarityimparting heteroatom, the oxygen, as well the presence of a carbonyl moiety.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The response surface generated for percentage of film formation (Figure 05) for fuel and concentration showed that high percentage of film formation is reached for the concentration levels above of center and high point. These results are consistent with the literature [4,5,6,8]. The biodiesel lubricity is due to the presence of a polarityimparting heteroatom, the oxygen, as well the presence of a carbonyl moiety.…”
Section: Resultssupporting
confidence: 93%
“…However, statistical errors observed in the model used were higher than expected (0.05 for 95% level of confidence). The trend of responses corresponds to that proposed by previous studies in this area [4][5][6]8]. It means that the friction coefficient decreases as the concentration of biodiesel increases.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These formulations presented higher lubricity, contributing to a lower abrasive wear. According to these results, the low values in the wear are because the three polar groups of the type OH present in glycerin give it a better adsorption on the surface, consequently increasing the efficiency in the metal coating and improves lubrication capacity, protecting the surfaces 17 . Additionally the minimized evaporation effect for these formulations also contribute to generate these smaller scars.…”
Section: Worn Steel Disc Surface Analysismentioning
confidence: 96%
“…Mello et al 17 evaluated the tribological characteristics of 50, 500 and 1800 ppm sulfur diesel fuels and their mixtures with soybean biodiesel and sunflower biodiesel with mixtures of 5%, 20% and 100% by volume. The results showed that the wear and coefficient of friction (COF) increase with the reduction of the sulfur content in pure diesel.…”
Section: Introductionmentioning
confidence: 99%